A systematic review of emerging technologies in industrialized construction. (July 2021) - Qi, Bing; Razkenari, Mohamad; Costin, Aaron; Kibert, Charles; Fu, Meiqing
Abstract: Industrialized construction, because of its factory-based nature, has significant potential for successful adoption of emerging technologies compared to traditional construction. The main objective of this review is to identify the current mainstream research directions and research gaps in applying emerging technologies in industrialized construction. This review classifies and analyzes 102 relevant articles published in the construction management-related journals in the last 15 years (i.e. 2004-2019) according to technology types, structural systems, project phases, and application fields. Results indicate there are apparent differences in the utilization level of different technology types, the research focus for different project phases, and the number of articles for different structural systems. Major benefits and challenges for different application fields are also discussed. This review identifies several research gaps, including less focus on specific structural systems or technologies, inadequate research on performance assessment measures, and a lack of effective training programs. Significantly, this review provides a roadmap for future research, with specific short-term and long-term solutions to address the identified research gaps. Highlights: The main objective of this review is to identify the current mainstream research directions and research gaps in the application of emerging technologies in industrialized construction. Results indicate there are apparent differences in the utilization level of different technology types, the research focus for different project phases, and the number of articles for different structural systems. Major benefits and challenges for different application fields are also discussed Several major research gaps and recommendations for future works have been identified.